Impact of previous biologic use and body weight on the effectiveness of guselkumab in moderate-to-severe plaque psoriasis: a real-world practice. (September 2021) - Hung, Yi-Teng; Lin, Yu-Jr; Chiu, Hsien-Yi; Huang, Yu-Huei
Background: Real-life data on patients with psoriasis treated with guselkumab are few and are needed to compare with trial-based data. We investigated the effect of clinical factors on real-world effectiveness of guselkumab. Methods: This multicentre study retrospectively included 135 patients with psoriasis treated with guselkumab from June 2018 until November 2020. Effectiveness was assessed using the degree of improvement in the Psoriasis Area and Severity Index (PASI) scores at baseline and after 4, 12, 20, 28, and 36 weeks. Predictors of effectiveness were also evaluated. Results: At week 36, 67% of the patients achieved PASI 75. Multivariate logistic regression analysis revealed that heavier patients were less likely to achieve PASI 75 at week 4 than patients with lower body weights. Fewer patients exposed to only one biologic achieved PASI 75 at weeks 4, 20, 28, and 36 [odds ratio (OR) = 0.08 (95% CI, 0.01–0.48), 0.21 (95% CI, 0.05–0.74), 0.04 (95% CI, 0.00–0.35), and 0.07 (95% CI, 0.00–0.68), respectively] than biologic-naïve patients. Patients previously treated with more than one biologic were less likely to achieve PASI 75 at weeks 12, 20, 28, and 36 [OR = 0.05 (95% CI, 0.01–0.22), 0.03 (95% CI, 0.01–0.16), 0.00 (95% CI, 0.00–0.03), and 0.00 (95% CI, 0.00–0.044), respectively] than biologic-naïve patients. Patients with previous anti-interleukin (IL)-17 exposure, rather than tumour necrosis factor-α and IL-12/23 inhibitors, had lower PASI improvements to guselkumab than biologic-naïve patients at weeks 12, 20, and 28 [OR = 0.19 (95% CI, 0.03–0.90), 0.10 (95% CI, 0.02–0.55), and 0.03 (95% CI, 0.00–0.29), respectively]. Conclusions: The effectiveness of guselkumab was compromised in a real-world setting. Delayed onset of therapeutic response was noted in heavier patients. Biologic exposure, the number of previously used biologics, and previous exposure to IL-17 inhibitors were clinical predictors of a reduced response to guselkumab. Physicians may share this information with patients to make treatment decisions.